Can Narratoscepticism Be a Valid Alternative? A Critique of Strawson’s Episodicity Argument - Lukić, Vladimir (Conatus - Journal of Philosophy, 2024)
This paper argues against Galen Strawson’s criticism of the narrativist identity thesis. Strawson points out that the narrativist thesis fails to portray those with an episodic perception of themselves. I claim that episodicity is rather problematic and that we should question the validity of this notion. The first step in this goal is to decipher Strawson’s basis of the self which is an amalgam between the cultural and social and is perceived differently by different people. Afterwards, I will try to use the claims derived from Strawson’s basis and apply the critique of his method. I pose a question about the relationship between episodic and diachronic and, ultimately, argue that both culturally and biologically, assuming the diachronic aspect of the self is necessary, apart from the very small number of cases. In this sense, the main conclusion is that Strawson’s thesis is limiting but does not pose a valid alternative to the narrativist identity thesis.